1993
DOI: 10.1159/000187559
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin Treatment and Amino Acid Metabolism in Hemodialysis Patients

Abstract: A previous report suggests that treatment with recombinant human erythropoietin (rH-EPO) significantly improves many abnormalities in circulating amino acids (AA) in hemodialysis patients. We evaluated the effects of a 12-month treatment with rH-EPO (150-250 U/kg/week) on blood AA levels in 10 patients with chronic renal failure under regular dialytic treatment. During treatment, hemoglobin levels increased from 7.0 ± 0.3 to 10.1 ± 0.3 g/dl at 3 months remaining steady thereafter. Before the treatment, patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9] Altered plasma amino acid concentrations have also been reported in dogs with experimentally induced or naturally occurring renal failure that has been managed conservatively. [1][2][3][4][5][6][7][8][9] Altered plasma amino acid concentrations have also been reported in dogs with experimentally induced or naturally occurring renal failure that has been managed conservatively.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Altered plasma amino acid concentrations have also been reported in dogs with experimentally induced or naturally occurring renal failure that has been managed conservatively. [1][2][3][4][5][6][7][8][9] Altered plasma amino acid concentrations have also been reported in dogs with experimentally induced or naturally occurring renal failure that has been managed conservatively.…”
mentioning
confidence: 99%
“…We read with interest the paper by Garibotto et al [1] on the treatment with recombinant human erythropoietin (rHuEPO) and amino acid metabolism in hemodialysis patients. The paper concluded that amino acid imbalance in dialysis patients was not improved with rHuEPO treatment.…”
Section: Dear Sirmentioning
confidence: 99%
“…In hemodialysis patients, studies on rHuEPO treatment have produced varied results. While one study reported improvement in amino acid imbalance [3], another reported no change [1]. Yet another reported no change in biochemical nutritional indices [4].…”
Section: Dear Sirmentioning
confidence: 99%
“…Although their hematocrit rose from 0.18 to 0.28. there was no weight increase nor improvement in serum urea nitrogen or serum creatinine. The benefi cial effects of EPO may have been blunted by a modest but uncorrected degree of metabolic acidosis present in these patients [35], The effects of EPO on serum amino acid profile in MD patients remain controversial [36]. Therefore, EPO therapy may improve some nutritional parameters after at least 6 months of treatment, and this may not be observed if other metabolic disorders still remain uncor rected.…”
Section: Anorexiamentioning
confidence: 99%